How to develop a sustainable palladium-catalyzed cross-coupling reactions for active ingredient manufacture - Steven, Alan (Frontiers in Catalysis, 2025)
This Perspective reflects on practices that lead to the development of high turnover cross-coupling catalytic cycles involving palladium. These processes are attractive for the manufacture of agrochemical, human or veterinary active ingredients, and in some respects are more sustainable than alternatives that use base metals at much higher loadings. The practices are structured in terms of important elements of the workflow for developing a cross-coupling for commercialization, and are discussed using the key metrics that drive catalytic efficiency and sustainability. Realistic opportunities and challenges for metal recovery and reuse are also among the messages discussed.